Structural elucidation of a major active compounds from the stem barks of Entada spiralis Ridl - Mat So'ad, Siti Zaiton; Harun, Aiza; Mohd Hassan, Norazian; Che Mohd Ramli, Neni Kartini (2011)
Bioassay-guided isolation of methanol extract revealed that medium polar fraction of the extract contained a few compounds that inhibited the growth of dermatophytes skin caused diseases. This confirmed the traditional usages of the stem barks of Entada spiralis by Malays in the old time, as a soap, shampoo and scrub during the treatment of skin problems. Minimum inhibitory concentration of the fraction gave a significant value for the effect on selected dermatophytes which are T. rubrum, T. mentagrophytes and M. gypseum. Out of the five bioactive compounds isolated we will discuss one(1)of the compound which is proposed as a novel compound. The structural elucidation of the compound were based on spectroscopic analysis by using 1H-NMR, 13CNMR, DEPT, HMBC and HMQC. The mass spectrum, FTIR and UV were also used to support our data. From the structural elucidation,the compound is suggested as a triterpenoidal saponin which has never been reported elsewhere.